Síntese de nano-suportes poliméricos heterofuncionais para a imobilização da Lipase B de Candida antarctica - Everton, Stefanni de Sousa (2021)
Heterofunctional nano-supports have emerged in the enzyme immobilization scenario due to the minimization of problems such as diffusion difficulties and low specific area. In addition, these materials are promising due to their ability to specifically interact with the surface of lipases. Therefore, this study aimed to synthesize heterofunctional nano-supports using the monomers methyl methacrylate (MMA), divinylbenzene (DVB), and the functional monomer glycidyl methacrylate (GMA), to develop promising support for use in enzyme immobilizations. In addition, it was sought to find the best support/enzyme ratio as a function of the degree of hydrophobicity and surface functionality. Based on the results of this study, PMMA, P(MMA-co-DVB) and P(MMMA-co-DVB-co-GMA) nano-supports were synthesized with 25 % and 50 % of GMA, thus varying the concentration of the epoxide group belonging to GMA. Finally, the nano-supports produced had their performances evaluated in hydrolysis and esterification reaction, after immobilization of the enzyme lipase from Candida antarctica type B (CAL B). As a result, it was observed that the nanobiocatalysts containing the epoxide group showed better performances, presenting high specific areas, pronounced pore volumes and diameters, and hydrophilic nature. Furthermore, no direct relationship was observed between the degree of hydrophobicity and the activity of the biocatalysts. Thus, it was found that the epoxide group provided a better performance of the biocatalysts by increasing the enzyme loading capacity and the interaction of this group with CAL B lipase.